Attack detection for cyber-physical systems: a zonotopic approach - Li, Jitao (2023)
This paper studies the problem of sensor attack detection for a class of cyber-physical systems with bounded perturbations. A novel attack detection method is proposed based on zonotopic reachability analysis. A false data injection attack is detected if there is no intersection between the predicted state set and the measurement state set. These sets are online calculated via zonotopic segments minimization. Two approaches, namely, projection and polytopic conversion, are presented to check the intersection situation. The detection performance is quantified using a stealthy attack set and the corresponding state estimation error set. Further, we consider replay attacks. To detect a replay attack, a watermark signal based active detection mechanism is introduced. Numerical simulations are conducted to demonstrate the validity of the proposed method.